Pervasive Mobile and Ambient Wireless Communications COST Action 2100 - Verdone, Roberto; Zanella, Alberto (Signals and Communication Technology, 2012)
Pervasive Mobile and Ambient Wireless Communications reports the findings of COST 2100, a project of the European intergovernmental COST framework addressing various topics currently emerging in mobile and wireless communications. Drawing on experience developed in this and earlier COST projects, the text represents the final outcome of collaborative work involving more than 500 researchers in 140 institutions and 30 countries (including outside Europe). The book's subject matter includes: • transmission techniques; • signal processing; • radio channel modelling and measurement; • radio network issues; and • recent paradigms including ultra-wideband, cooperative, vehicle-to-vehicle and body communications. The research reported comes from a variety of backgrounds: academic, equipment-manufacturing and operational. The information contained in this book will bring the study reported to a wider audience from all those spheres of work. Pervasive Mobile and Ambient Wireless Communications will be of interest to researchers for its cutting-edge analysis and to practitioners for its functional usability.